Modeling and optimization of Carbon in leach (CIL) circuit for gold recovery - Wadnerkar, D.; Tade, Moses; Pareek, V.; Utikar, R. (Elsevier Ltd, 2015)
Carbon in leach (CIL) is an important step in gold processing that involves simultaneous adsorption and leaching. While the mechanism of leaching and adsorption are well known, the effect of different operating and design parameters on the dynamics and performance of CIL circuit are not yet studied. The focus of this paper is to study the effect of operating parameters like cyanide concentration, oxygen concentration and mean particle diameter on the overall efficiency of CIL circuit. A dynamic model based on first principles is developed for the entire CIL circuit. Suitable kinetic models for both leaching and adsorption are adopted from the literature. Customizable simulator is written in MATLAB to simulate the model. Simulation results are first validated using previously published results. The validated model is then used to perform sensitivity studies on different parameters that affect the gold extraction process. The key parameters are optimized by conducting a multi-objective optimization study using elitist non-dominated sorting genetic algorithm of MATLAB. The percent recovery and net profit are maximized, while minimizing the cyanide used in the process. Four decision variables are used viz. particle diameter, oxygen concentration, cyanide concentration and ore volume fraction in tanks. A Pareto-optimal solution for the process parameters is provided such that all the objectives are improved to a value above which their improvement will result in degradation of other objectives. As a result, high recovery, high profit and low cyanide concentrations can be achieved simultaneously.